2017
DOI: 10.18203/2320-6012.ijrms20174962
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of hollow viscus injury due to blunt trauma abdomen

Abstract: Background: Blunt trauma abdomen is one of the most common causes of morbidity and mortality among younger age group. Hollow viscus injury is one of the most common cause of mortality following blunt trauma abdomen. The Objective of this research was to study clinical presentation, diagnostic methods, treatment modalities and outcome of hollow viscus injury following blunt trauma abdomen. Methods: All patients with hollow viscus injury were included in this study, All the clinical, operative and postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…25 were selected for non-operative management. Kurane and Ugane (2017) showed that Ileum was the most commonly site of perforation, and postoperative complications were seen in 66% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…25 were selected for non-operative management. Kurane and Ugane (2017) showed that Ileum was the most commonly site of perforation, and postoperative complications were seen in 66% of patients.…”
Section: Discussionmentioning
confidence: 99%